Harga Diri Dan Interaksi Sosial Ditinjau Dari Status Sosial Ekonomi Orang Tua - Sugeng Widodo, Agustinus (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This study aims to findout a correlation between self-esteem and social interaction, and differences the two variables on the socioeconomic status of parents. The subjects in this study were students of SMK Petra Christian Surabaya number of 208 students. Data collection techniques in this study using the scales of social interaction and self-esteem. Data that has been collected will be analyzed statistically the product moment correlation and Anova. The results showed: first, there are  positive correlation signify-cantly between self-esteem and student’s social interaction.         Second, showed that there are differences between the self-esteem of students who apply for tuition assistance to students who do not apply for tuition assistance. Third, showed that there are differences of social interaction between the students who apply for tuition assistance to students who do not apply for tuition assistance.Keywords: social interaction, self-esteem and parental socioeconomic status